Analysis of Pakistan’s policy towards Afghan refugees: a legal perspective - Azam, Raja Irfan (Riga Graduate School of Law, 2021)
Pakistan hosts to the world's largest single population of Afghan refugees. However, despite Pakistan's long-standing acknowledgment of Afghan refugees, their legal status remains unclear. This is due to Pakistan's refusal to sign either the 1967 Protocol Relating to the Status of Refugees or the United Nations Convention Relating to the Status of Refugees (also known as the Geneva Convention). This paper investigates whether Pakistan's approach against Afghan refugees is in accordance with international law and human rights principles. Moreover, this paper seeks to provide a comprehensive response to the above question by highlighting the many difficulties that Afghan refugees have encountered as a result of a lack of consistent refugee legislation protecting their rights and providing recommendations on how the situation of Afghan refugees can be improved. Pakistan hosts to the world's largest single population of Afghan refugees. However, despite Pakistan's long-standing acknowledgment of Afghan refugees, their legal status remains unclear. This is due to Pakistan's refusal to sign either the 1967 Protocol Relating to the Status of Refugees or the United Nations Convention Relating to the Status of Refugees (also known as the Geneva Convention). This paper investigates whether Pakistan's approach against Afghan refugees is in accordance with international law and human rights principles. Moreover, this paper seeks to provide a comprehensive response to the above question by highlighting the many difficulties that Afghan refugees have encountered as a result of a lack of consistent refugee legislation protecting their rights and providing recommendations on how the situation of Afghan refugees can be improved.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Refugee protection; Afghanistan; Pakistan